Modulação do retinol na lesão da barreira morfofuncional induzida pela toxina A do Clostridium difficile em culturas de células intestinais - Maciel, Andressa Aby Farraj Linhares (2007)
Vitamin A (retinol) is an essential nutrient that is necessary in small amounts for normal functioning of the visual system, immune function and reproduction. Our group has investigated the effect of oral dosis of vitamin A on the early childhood diarrhea in our prospective community-based studies in high endemic areas in the Northeast of Brazil and has found a benefit of retinol therapy in reducing the mean duration but not the incidence of diarrheal episodes. In this study, we have explored the role of retinol supplementation in intestinal cell lines, following Clostridium difficile toxin A (TxA) cytotoxic challenge. C. difficile is the most common anaerobic pathogen that causes antibiotic-associated diarrhea and pseudomembranous colitis. We have focused on changes in transepithelial electrical resistance (TER) in Caco-2, a more differentiated intestinal cell line, and on models of proliferation, migration and cell death in IEC-6 cells, an undifferentiated crypt cell line, following or not by TxA-induced cell injury. The results showed retinol alone increased the TER, cell migration and proliferation, and also promoved significant reduction of apoptosis and necrosis, however this effect was not observed at the cell proliferation. To study the retinol effect on the TxA-induced loss of TER, cells were exposed during 24h to 0,1μg/mL TxA. Retinol improved TER (% of initial value) at the concentrations of 0,1nM and 0,3nM at 3h (59,3±1,3; 69,8±0,6 vs 59,3±1,3Ωcm2, respectively), and at 4h (36,1± 0,02; 33,5± 1,8 vs 27,3±0,2Ωcm2, respectively) in relation to the untreated control challenged with TxA. During this time there was no influence of the cell proliferation in the Caco-2 cells. Retinol increased cell proliferation after TxA-induced cell damage (0,1μg/mL) at a rate of 14,2%, 23,8%, 59,8%; 8,4%; 30,2%; 44,1% after 24h (doses of 0,01; 0,03; 0,1; 1,0; 10; 100nM of retinol, respectively), compared to controls only with TxA. After 24h of TxA exposure (0,01μg/ml), following plate scraping, the retinol supplementation improved significantly IEC-6 migration at the concentrations of 0,1-100nM in rate of 30-80% and 60-100%, in 12h and 24h, respectively. Retinol reduced TxA-induced apoptosis and necrosis at the concentration of 0,03: 0,1; 1; 10 and 100nM, p<0.05, in comparison to the control with TxA. These results suggest that retinol has a critical role in reducing apoptosis, improving cell migration and proliferation and preventing the reduction in TER, following TxA challenge, suggesting that vitamin A is an essential nutrient to protect the intestinal epithelial barrier function.